Indonesian Islamic Commercial Banks’ Efficiency: A Stochastic Frontier Analysis - Sylva Alif Rusmita; Devy Ariesta Putri (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Islamic banks in Indonesia are continuously experiencing a rapid growth; thus, it results in a competitive financial sector. Consequently, maintaining an excellent performance is a prerequisite to gain customers’ trust and loyalty, one of the ways is enhancing productivity and efficiency performance. Drawing on this issue, the present study aims to examine the efficiency of Islamic banks listed in the Financial Services Authority (OJK) in the period of 2015 to 2019. Employing Stochastic Frontier Analysis (SFA) as a parametric approach, this study measured the efficiency level of cost and profit efficiency of the Indonesian Islamic commercial banks. The data were a cross-section and panel data obtained from financial reports established by seven Indonesian Islamic commercial banks. The result of frontier analysis on the efficiency costs showed that the value of sharia banks’ average efficiency in Indonesia was approximately 93.41%, while the efficiency of profit resulted in 55.35%. These results suggest that Islamic banks tend to be efficient in controlling costs from the year of 2015 to 2019. It is a worth saying that this study’s results contribute to providing fruitful insights for Islamic banks to increase their efficiency by controlling their cost of production such as the cost of funds and cost of operation.